Clinical implementation of coverage probability planning for nodal boosting in locally advanced cervical cancer. Issue 1 (April 2017) - Ramlov, Anne; Assenholt, Marianne S.; Jensen, Maria F.; Grønborg, Caroline; Nout, Remi; Alber, Markus; Fokdal, Lars; Tanderup, Kari; Lindegaard, Jacob Chr.
Abstract: Purpose: To implement coverage probability (CovP) for dose planning of simultaneous integrated boost (SIB) of pathologic lymph nodes in locally advanced cervical cancer (LACC). Material and methods: CovP constraints for SIB of the pathological nodal target (PTV-N) with a central dose peak and a relaxed coverage at the perimeter were generated for use with the treatment planning system Eclipse: PTV-N D98 >90%, CTV-N D98 >100% and CTV-N D50 >101.5% of prescribed dose. Dose of EBRT was 45 Gy/25 fx with a SIB of 55–57.5 Gy depending on expected dose from brachytherapy (BT). Twenty-five previously treated patients with 47 boosted nodes were analysed. Nodes were contoured on cone beam CT (CBCT) and the accumulated dose in GTV-NCBCT and volume of body, pelvic bones and bowel receiving >50 Gy (V50) were determined. Results: Nearly all nodes (89%) were visible on CBCT and showed considerable concentric regression during EBRT. Total EBRT and BT D98 was >57 GyEQD2 in 98% of the visible nodes. Compared to treatment plans aiming for full PTV-N coverage, CovP significantly reduced V50 of body, bones and bowel ( p  < 0.001) Conclusion: CovP is clinically feasible for SIB of pathological nodes and significantly decreases collateral SIB dose to nearby OAR.